2016
DOI: 10.1302/0301-620x.98b1.36336
|View full text |Cite
|
Sign up to set email alerts
|

Cemented or cementless humeral fixation in reverse total shoulder arthroplasty?

Abstract: This study demonstrates that uncemented stems have at least equivalent clinical and radiographic outcomes compared with cemented stems when used for reverse total shoulder arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…22 Furthermore, two recent studies showed that uncemented humeral stems have equivalent clinical and radiographic outcome compared to cemented stems in the shortand midterm, but have the advantages of shorter operation time, better biological ingrowth potential and easier to revise when necessary. 9,23 In our longterm followup study only one humeral stem was revised.…”
Section: Discussionmentioning
confidence: 92%
“…22 Furthermore, two recent studies showed that uncemented humeral stems have equivalent clinical and radiographic outcome compared to cemented stems in the shortand midterm, but have the advantages of shorter operation time, better biological ingrowth potential and easier to revise when necessary. 9,23 In our longterm followup study only one humeral stem was revised.…”
Section: Discussionmentioning
confidence: 92%
“…22 The results reported here confirm that the short-term clinical outcomes at an average 3 years of follow-up is comparable with those obtained with the Grammont design. 5,6,9,10,12,15,[17][18][19][22][23][24][25][26][27] This stem still requires longer term follow-up to confirm these initial findings. Interestingly, internal rotation appears improved with the short-stem press-fit component compared to the Grammont design.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Loosening of the prosthetic components can cause pain and loss of function, although aseptic loosening is rare during the initial postoperative years. [17][18][19][20] Location of the pain can guide the surgeon in the diagnosing process. Thus, pain in the proximal part of the upper arm can indicate humeral loosening, spontaneous periprosthetic fracture or infection; pain over the scapula can indicate a fracture of the spine of scapula or suprascapular nerve irritation by the superior screw of the glenoid component.…”
Section: Analysis and Aetiology Of Painmentioning
confidence: 99%